Effects of allergic diseases and age on the composition of serum IgG glycome in children - Pezer, Marija; Stambuk, Jerko; Perica, Marija; Razdorov, Genadij; Banic, Ivana; Vuckovic, Frano; Gospic, Adrijana Miletic; Ugrina, Ivo; Vecenaj, Ana; Bakovic, Maja Pucic; Lokas, Sandra Bulat; Zivkovic, Jelena; et al. (Scientific reports, 2016)
It is speculated that immunoglobulin G (IgG) plays a regulatory role in allergic reactions. The glycans on the Fc region are known to affect IgG effector functions, thereby possibly having a role in IgG modulation of allergic response. This is the first study investigating patients’ IgG glycosylation profile in allergic diseases. Subclass specific IgG glycosylation profile was analyzed in two cohorts of allergen sensitized and non-sensitized 3- to 11-year-old children (conducted at University of Aberdeen, UK and Children’s Hospital Srebrnjak, Zagreb, Croatia) with 893 subjects in total. IgG was isolated from serum/plasma by affinity chromatography on Protein G. IgG tryptic glycopeptides were analyzed by liquid chromatography electrospray ionization mass spectrometry. In the Zagreb cohort IgG glycome composition changed with age across all IgG subclasses. In both cohorts, IgG glycome composition did not differ in allergen sensitized subjects, nor children sensitized to individual allergens, single allergen mean wheal diameter or positive wheal sum values. In the Zagreb study the results were also replicated for high total serum IgE and in children with self-reported manifest allergic disease. In conclusion, our findings demonstrate no association between serum IgG glycome composition and allergic diseases in children.